Cost-Effectiveness Analyses of Home Parenteral Nutrition for Incurable Gastrointestinal Cancer Patients - Li, Wenqian; Guo, Hanfei; Li, Lingyu; Cui, Jiuwei (Frontiers in Oncology, 2022)
Background Appropriate nutritional support, including supplemental home parenteral nutrition (sHPN), may improve prognosis and quality of life (Qol) of malnourished cancer patients. We aimed to explore the cost-effectiveness of sHPN for incurable gastrointestinal cancer patients from the Chinese healthcare perspective. Method Clinical data were extracted from a randomized controlled trial (NCT02066363). Patients were randomized into the sHPN group or the non-sHPN group (receiving best practice nutritional care). A Markov model was established with a 6-week cycle length. Costs were acquired from local hospitals, effect parameters included quality-adjusted life year (QALY), Qol, body mass index, fat-free mass (FFM), FFM index, handgrip strength, and a 6-min walking test. Sensitivity analyses were conducted with a willingness-to-pay (WTP) set at 3 per capita gross domestic product (29,307/QALY). Results When considering QALY as a utility, the incremental cost-effectiveness ratio (ICER) was 24,289.17, with an incremental cost of 2,051.18 and an incremental QALY of 0.0844 between the sHPN group and the non-sHPN group. Furthermore, we explored the cost-effectiveness of sHPN from multidimensions, where we analyzed various effect parameters at different visits; the results showed a superior benefit for patients in the sHPN group except for the handgrip parameter at visit 2. Sensitivity analysis demonstrated the influence of utilities in the sHPN group, but the sHPN group was still cost-effective with a WTP of 2,500/QALY. Conclusion In China, sHPN was cost-effective for patients with incurable gastrointestinal cancer, which suggested further applications in clinical practice and provided references for clinical decisions and pricing.